Emerging Cyber Threats in Bangladesh: In Quest of Effective Legal Remedies - Maruf, Ashiquddin Mohammad; Islam, Md Rabiul; Ahamed, Bulbul (Northern University Journal of Law, 2014)
With the advent of technology human beings are becoming exclusively dependant on automation and we can see its influence on all spheres of our life. The history of automation began when Babbage invented computer and especially a new horizon was opened before us with the invention of network particularly the Internet and World Wide Web (WWW). Internet has become the backbone of all kinds of communication systems and it is also one of the most important sources of knowledge in the present digitalized world. DOI: http://dx.doi.org/10.3329/nujl.v1i0.18529 Northern University Journal of Law Vol.1 2010: 112-124